CCAFS Agriculture Monitor (CAM) - Aggarwal, Pramod K.; Shirsath, Paresh Bhaskar; Vyas, Shalika; Arumugam, Ponraj; Goroshi, Sheshakumar (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
A report o weather deviations and crop loss assessment for area yield index insurance schemes in India. The report is structured in three sections. First section presents weather parameters, second section describes the crop condition and crop specific conditions of prevented sowing, sowing failure and final yield estimates are described thereafter.